2015
DOI: 10.1111/dote.12418
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid minimally invasive esophagectomy for cancer: impact on postoperative inflammatory and nutritional status

Abstract: The purpose of this case-control study was to evaluate the impact of hybrid minimally invasive esophagectomy for cancer on surgical stress response and nutritional status. All 34 consecutive patients undergoing hybrid minimally invasive esophagectomy for cancer at our surgical unit between 2008 and 2013 were retrospectively compared with 34 patients undergoing esophagectomy with open gastric tubulization (open), matched for neoadjuvant therapy, pathological stage, gender and age. Demographic data, tumor featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…Preoperative albumin concentration is a well known prognostic marker; however, fewer studies have assessed the prognostic value of postoperative albumin. Although a decrease in albumin after surgery probably reflects the systemic inflammatory response to surgery and was associated with higher‐grade complications, decreased albumin levels have been shown to be associated with other adverse outcomes and were independently predictive of survival in multivariable analysis in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…Preoperative albumin concentration is a well known prognostic marker; however, fewer studies have assessed the prognostic value of postoperative albumin. Although a decrease in albumin after surgery probably reflects the systemic inflammatory response to surgery and was associated with higher‐grade complications, decreased albumin levels have been shown to be associated with other adverse outcomes and were independently predictive of survival in multivariable analysis in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…A total of 24 studies with 7117 patients were involved in the analysis of all‐cause RCs. Figure a shows that the patients who underwent MIE experienced less postoperative RCs as compared to those who underwent OE (OR = 0.56; 95% CI = 0.41, 0.78; P = <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 studies with 6925 patients were included in the analysis of all‐cause AL, which showed low level of heterogeneity ( P = 0.08, I 2 = 32%) and no statistical difference between MIE versus OE (OR = 1.08; 95% CI = 0.92, 1.26; P = 0.35) (Figs b, S2c). Data for all‐cause CCs was reported in 13 studies with 2302 patients and showed neither heterogeneity ( P = 0.99, I 2 = 0%), nor statistically significant difference between MIE or OE (OR = 0.97; 95% CI = 0.74, 1.26; P = 0.81) (Figs a, S2d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details concerning surgical techniques have been published elsewhere . Briefly, esophagectomy was carried out using an Ivor Lewis procedure, by laparotomy or laparoscopy, and right thoracotomy for tumors of the mid‐lower esophagus and the gastric cardia . During surgical procedures, biopsies of periesophageal adipose tissue and of tumoral and nontumoral mucosa were collected for each patient.…”
Section: Methodsmentioning
confidence: 99%